The effect of sports massage with meditation on myalgia disorders - Ali Satia Graha; Rina Yuniana (MEDIKORA, 2021)
Myalgia is pain that occurs in the muscles that can interfere with daily activities. Sports massage and meditation is an alternative to reduce the feeling. The purpose of this study was to determine the effect of sports massage on overcoming myalgia disorders. This study uses a quantitative quasi-experimental method with this type of design using the equivalent time series sample design. The population in this study was a total of 36 masseurs who worked in sports injury therapy massage centers on the 4th floor of UNY Plaza. The sample was determined using purposive sampling technique and obtained a number of 15 samples. This type of research is a quasi-experimental, using a pretest-posttest design. Research subjects were given 3 (three) repetitions of treatment, namely the first week, the second week and the third week. The data analysis technique in this study used a t-test (paired t-test), in test I, test II and test III, the overall significance was obtained with a value of 0.000 (sig. 0.05). The conclusion in this research is sports massage with meditation can reduce myalgia disorders.Pengaruh sports massage dengan meditasi terhadap gangguan myalgiaAbstrakMyalgia merupakan nyeri yang terjadi pada otot yang dapat menganggu aktivitas sehari-hari. Sports massage dan meditasi merupakan salah satu alternatif untuk mengurangi rasa nyeri. Tujuan penelitian ini untuk mengetahui pengaruh sports massage dengan meditasi terhadap gangguan myalgia. Penelitian ini menggunakan metode quasi eksperimen kuantitatif dengan jenis rancangan menggunakan the equivalent time series sample design. Populasi dalam penelitian ini adalah masseur sejumlah total 36 yang bekerja di tempat masase terapi cedera olahraga di Plaza UNY lantai 4. Penentuan sampel menggunakan teknik purposive sampling dan diperoleh sejumlah 15 sampel. Subjek penelitian diberikan 3 (tiga) kali pengulangan perlakuan yaitu minggu ke- I, minggu ke-II dan minggu ke-III. Teknik analisis data dalam penelitian ini menggunakan uji-t (paired t-test). pada uji I diperoleh nilai 0,000 (sig. 0,05), uji II diperoleh nilai 0,000 (sig. 0,05) dan uji III diperoleh nilai 0,000 (sig. 0,05). Kesimpulan dalam penelitan ini adalah sports massage dengan meditasi dapat mengurangi gangguan myalgia